Redox Activity of Sodium Vanadium Oxides towards Oxidation in Na Ion Batteries - Adamczyk, Evan (Materials (Basel), 2018)
The search for new materials that could be used as electrode material for Na-ion batteries is one of the most challenging issues of today. Many transition metal oxide families as well as transition metal polyanionic frameworks have been proposed over the last five years. In this work, we report the sodium extraction from Na(2)V(3)O(7), which is a tunnel type structure built of [V(3)O(7)](2−)(∞) nanotubes held by sodium ions. We report a reversible charge capacity of 80 mAh/g at 2.8 V vs. Na(+)/Na due to the V(5+)/V(4+) redox activity. No oxygen redox activity has been observed for this material nor for the vanadium (5+) oxide Na(4)V(2)O(7).